Indoor Environmental Quality & Occupant Satisfaction in Green Building (Case Study: Company X at East Jakarta, DKI Jakarta) - Yuniar Widya Larasati; Rachmadhi Purwana; Ahyahudin Sodri (Jurnal Penelitian Pendidikan IPA, 2023)
The global movement in green building development has been going on since the early 1960s. Although initially driven by environmental agendas such as carbon and energy, there is a growing acknowledgment that green buildings can affect Indoor Environmental Quality (IEQ). Many researchers also state that improved indoor environmental quality is associated with better occupant satisfaction. However, some localized green buildings, especially in developing countries, often don’t recognize IEQs and occupant satisfaction as important issues, so they remain unstudied. Therefore, this study aimed to evaluate the performance of IEQ and occupant satisfaction. The analytical methods used were descriptive statistics and regression analysis. The outcome demonstrated that green building standards do not automatically improve indoor environment quality, particularly when the lighting parameter is below the limit values. The analysis findings showed that most respondents expressed their satisfaction with IEQ and significantly influenced occupant satisfaction. In addition, this research contributes to the development of green building evaluation practices that prioritize environmental health and occupant satisfaction